Rural school-community relationships : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education in Education at Massey University - Frater, Garry Kingsley (Massey University, 1979)
The Wanganui Education Board Annual Report for the Year Ended 31st January 1977 stated: "Without wishing to overstate the problem, it is worth recording that recent years have been marked by an increasing incidence of breakdown of amicable relationships between teachers and local communities." This study examines the area of rural education, and particularly that of rural school - community relationships in order to ascertain the 'nature, 'extent', 'reasons' and 'possible actions to help alleviate' such breakdowns occurring. The literature discussing rural education in New Zealand reveals the preoccupation of educational authorities since the time of early settlement with ensuring the country child receives a level of educational opportunity equal to his urban counterpart. Rural principals in the Wanganui Education Board in response to a questionnaire indicated their viewpoints on a range of matters related to 'living' and 'teaching' in rural communities. While many areas of satisfactions with living and teaching in rural communities were expressed, the 'morale' of rural principals appears to have been adversely affected, by such factors as the escalating cost of living and the status and promotion opportunities perceived in the proposed 'broadbanding' scheme. To ascertain the viewpoints of parents on a range of matters related to rural education, interviews were conducted with 17 school committees in the Wanganui Education Board district. The parents perceived the most important qualities of a rural principal to be: an ability to fit into a country community and communicate with its people; and having an attitude of interest and concern in the school and community. They also expressed a desire for more say in the appointment and termination of staffing. To determine the 'nature' and 'extent' of rural school - community relationship difficulties, data was solicited by questionnaire from N.Z.E.I. Counsellors involved in cases 'related to' and 'affecting' such relationships. Problems relating to the broad areas of 'School Management' and 'School Programmes' together made up nearly three-quarters of the cases contributing to rural school - community relationship difficulty. Just over one quarter of the difficulties reported were resolved by the transfer of the teacher, yet in no case was transfer compulsory under the provisions of the Education Act. From the actual data supplied, on average one school in every 7.5 is experiencing a school - community relationship problem involving a counsellor during a four terms period. Advisers to Rural Schools and N.Z.E.I. Counsellors, in response to similar questionnaire items, gave their opinions as to possible 'reasons for' and 'actions to help alleviate' rural school - community relationship difficulties. On analysis, 10 broad categories of school and community behaviour that could provide reasons for breakdowns in relationships, were identified. Possible 'actions to help alleviate' such difficulties occurring were classified into 7 areas, a number of which may need to be effected, if there is to be an improvement. The complexity of human nature and the variables operating to complicate the issues in each situation preclude any simple answer as to why so many rural communities and their teaching staff are having relationship problems. It seems quite clear however, that in the current times of rapid social change, the rural school principal, staff and their families can find themselves, with their community members, especially if living at a distance from urban growth centres, less able to achieve and maintain living conditions, whether economic, social or environmental as in the past. Furthermore their conditions may not compare favourably with those in the urban sector. Such a climate is not conducive to attracting and retaining skilled teachers, a necessary component of good school - community relationships. The study concludes with a list of recommendations considered supportive of both the school and community, and hopefully the relationships between them.
Keywords: Rural schools, New Zealand; Primary schools, New Zealand; Community and school; Rural education, New Zealand